Frontispiece: Reverse Arene Sandwich Structures Based upon π‐Hole⋅⋅⋅[MII] (d8 M=Pt, Pd) Interactions, where Positively Charged Metal Centers Play the Role of a Nucleophile. Issue 13 (15th March 2019) - Rozhkov, Anton V.; Krykova, Mariya A.; Ivanov, Daniil M.; Novikov, Alexander S.; Sinelshchikova, Anna A.; Volostnykh, Marina V.; Konovalov, Mikhail A.; Grigoriev, Mikhail S.; Gorbunova, Yulia G.; Kukushkin, Vadim Yu.
Abstract : Reverse Sandwich Compounds In their Communication on page 4164 ff., V. Y. Kukushkin et al. show how square‐planar Pt II and Pd II systems give reverse sandwich structures in which the charge distribution at the metal and the arenes is opposite to that of classic sandwich species.